2012
DOI: 10.1177/0310057x1204000617
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Level Two and Level Three Checks of Anaesthesia Delivery Systems Performed at Three Hospitals in South Australia

Abstract: Anaesthetists may subject patients to unnecessary risk by not checking anaesthetic equipment thoroughly before use. Numerous adverse events have been associated with failure to check equipment. The Australian and New Zealand College of Anaesthetists and anaesthetic delivery system manufactures have made recommendations on how anaesthetic equipment should be maintained and checked before use and for the training required for staff who use such equipment. These recommendations are made to minimise the risk to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It has been documented that checks are not always conducted with the recommended protocol (Sweeney et al. ). Finally, the changes in proportion of incidents may be due to another variable which was not recorded, such as increased communication among students, staff, and clinicians (Haynes et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that checks are not always conducted with the recommended protocol (Sweeney et al. ). Finally, the changes in proportion of incidents may be due to another variable which was not recorded, such as increased communication among students, staff, and clinicians (Haynes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia services are performed in diverse and complex settings which need per case preparation and checking of equipment before use. 1,10 Anesthetists accomplish many tasks rapidly during induction of anesthesia, so the intense environment of the operating room, preparatory steps may be missed either unintentionally or possibly even intentionally to save time during emergency surgical procedures. 2 A Prospective study on anesthesia machine fault identification demonstrated that anesthesia machine check and equipment preparation before use continues to be a problem in the most operation room.…”
Section: Justificationmentioning
confidence: 99%
“…However, there is only a limited literature on the care provided by specialist anaesthetists, with much of it limited to small, single-centre studies focused on process outcomes rather than patient ones. For example, the quality of documentation by Australian anaesthetists varies 61 , as does adherence to guidelines for checking the anaesthesia machine 62 , sampling from arterial lines 63 and perioperative management of anticoagulant and antiplatelet drugs 64 .…”
Section: Is There An Issue With Australian Anaesthetists' Performance?mentioning
confidence: 99%